(untitled) (Società e diritti, 2022)
Abstract This contribution aims to analyse the relationship between sustainability and justice, in order to highlight its reflective character. In fact, there is no doubt that sustainability is the primary focus of the public debate, around which national and supranational strategies and practices are arranged; however, the semantic extension that this term has undergone risks confusing and finally dispelling its meaning. The contribution therefore focuses on the significant scope of the concept of sustainability, emphasizing its "open" character. The reference to openness thus becomes the hermeneutic key to granting sustainability and justice. If sustainability, therefore, is part of a particular representation of justice, the latter must reflexively become sustainable